2016
DOI: 10.1371/journal.pone.0161909
|View full text |Cite
|
Sign up to set email alerts
|

In Silico and Biochemical Characterization of Lysozyme-Like Proteins in the Rat

Abstract: BackgroundSpermatogenesis and sperm maturation in the male reproductive tract is dictated by a variety of proteins secreted in the testis and epididymis. Though the proteome of these tissues is known, the functional role of many of these proteins remains uncharacterized. In this study, we characterize the rat Lysozyme-like (Lyzl) genes and proteins.MethodsIn silico tools were used to predict the primary, secondary and tertiary structures. Reverse transcription PCR, immunofluorescence and immunoblotting were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Most of the c‐type LYZs are primarily expressed in the testis 13,14,27–30 . Among them, LYZL4, 14 LYZL6, 13 and SPACA3, also named SLLP1, 12 are found to be acrosomal proteins and are implicated in sperm–oocyte fertilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the c‐type LYZs are primarily expressed in the testis 13,14,27–30 . Among them, LYZL4, 14 LYZL6, 13 and SPACA3, also named SLLP1, 12 are found to be acrosomal proteins and are implicated in sperm–oocyte fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, androgens also modulate mouse Lyzl4 32 . Rat Lyzls were once found to be androgen‐regulated genes, 33 but another study indicated that they are not 29 …”
Section: Discussionmentioning
confidence: 99%
“…ARHGEF10 encodes a Rho guanine nucleotide exchange factor that may be involved in neural morphogenesis 55 . LYZL1 belongs to the family of lysozyme-like proteins that are implicated in sperm function and innate immunity 56 . According to GeneCards (GCID: GC09P020659), FOCAD encodes a tumor suppressor gene that is highly expressed in the brain.…”
Section: Discussionmentioning
confidence: 99%